EFFECT OF DIFFERENT ESTABLISHMENT METHODS AND NITROGEN LEVELS ON YIELD ATTRIBUTES, YIELD, NUTRIENT UPTAKE AND ECONOMICS OF RICE - E. NARSAIAH, CH. RAMULU, P. RAGHU RAMI REDDY and (The Journal of Research, PJTSAU, 2020)
A research experiment was conducted on rice during kharif 2015-17 at Regional Agricultural Research Station, Warangal (Telangana) under different establishment methods (machine transplanting, conventional transplanting, drum seeding and broadcasting) with three nitrogen levels (120,160 and 200 kg ha-1). Significantly higher number of panicles m-2 (317), grains per panicle (277), grain yield (5345 kg ha-1) and straw yield (6305 kg ha-1) were recorded in machine transplanting over other establishment methods. With increase in levels of nitrogen, the yield and yield attributes also showed an increase upto 200 kg N ha-1 but found on par with 160 kg N ha-1. The net income (Rs.64,587) as well as B:C ratio (1:3.1) was maximum with machine transplanting closely followed by broadcasting (1:3.0).